Ship manoeuvring in shallow water with ship-bank interaction effects - Adi Maimun Abdul Malik, author; A. Priyanto, author; Rahimuddin, author; A. Baidowi, author; Nurcholis, author; International Conference on Ship Manoeuvring in Shallow and Confined Water (2009 : Antwerp, Belgium) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL